DISCURSO, CORPO E PODER: A OBJETIVAÇÃO/SUBJETIVAÇÃO DO SUJEITO HELEN KELLER SOB A PERSPECTIVA DOS ESTUDOS DISCURSIVOS FOUCAULTIANOS - Quadros, Suellen Fernanda de (2019)
In this work, we propose an analysis of statements - verbal and verbal-visual - that have discursively transformed the subject Helen Adams Keller, a North American deafblind woman, based on the Foucauldian Discursive Studies, more precisely in the formulations of Michel Foucault's archegenealogy. Thus, we draw a theoretical-analytical path around the processes of subjectivation of that philosopher, writer, lecturer and social activist, to decipher the relations of power-knowledge, domination and struggle within which discourses are established, function and produce subjects. Keller managed to reinvent his way of communicating and perceiving the world, achieving honors for his active participation in the struggle for the rights of people with disabilities and women. She and her teacher Anne Sullivan (the principal responsible for her performance) traveled the world by subscribing to discourses once restricted to some subject-positions, especially to a deafblind subject. Our analytical corpus consists of statements materialized in the film The Miracle of Anne Sullivan (1962) and in the autobiography The Story of My Life (2008); the chosen works depict the biography of Keller. The film gives more specifically to a part of his childhood, narrativized from the other's point of view / interpretation; and the book portrays, in addition to her childhood, her adult life through self-writing. In the regularity of the statements, we demonstrate how the intrinsic relation between power and resistance that focuses on the body, especially her gestures and attitudes, is consolidated in order to reinvent the history of a person who, being deaf and blind, would be doomed to live in the isolation imposed by an almost complete lack of communication. How and why did she become so famous? Which discourses, according to the corpus analyzed, contributed to her becoming one of the most important figures in the work of militancy in favor of people with disabilities? In order to answer these questions, we contextualize Keller's subject-position historically, analyzing the discursive and non-discursive practices that contributed to the objectivation / subjectivation processes, highlighting (i) the conducts and counter-conducts constitutive of the moment of language acquisition and, later , (ii) the practices of militancy, resistance and freedom, according to a writing of self, that enabled it to move from the condition of "savage" to a docility-utility relation, influencing the world through her discourses recorded in articles and books of her own.